Morphological Changes in Endothelial Cell Organelles in a No-Touch Saphenous Vein Graft - Sugaya,Akira (2022)
ABSTRACT Introduction: Improved long-term patency of the no-touch (NT) saphenous vein graft has been reported to result from the preservation of a healthy vascular microstructure, especially endothelial cells. However, the precise morphology of endothelial cells and their organelles in NT saphenous vein graft has not been fully investigated. In this study, we assessed the ultrastructure of preserved endothelial cells in saphenous vein graft using transmission electron microscopy. Methods: Intact control (IC) vein, NT saphenous vein graft, and conventional (CT) saphenous vein graft were harvested from a patient. After observation by light microscopy, the nuclei and mitochondria in the preserved endothelial cells were compared among IC, NT, and CT using transmission electron microscopy, and the endothelial organelles were assessed quantitatively. Results: Light microscopy showed that the preservation of endothelial cells was comparable in IC, NT, and CT. Subsequent transmission electron microscopy observation showed that the nuclei in preserved endothelial cells appeared more swollen in CT than that in NT. Quantitative analysis revealed that nuclear size and circularity of preserved endothelial cells in NT and IC were similar, but those in CT were larger and higher, respectively, than those in IC and NT. In addition, the mitochondrial size in preserved endothelial cells in CT was larger than that in IC and NT. Conclusion: Necrotic changes in endothelial organelles characterized by swelling of nuclei and mitochondria were prominent in CT saphenous vein graft. The normally maintained ultrastructure of preserved endothelial cells in NT saphenous vein graft could contribute to long-term patency.